2021
DOI: 10.1158/0008-5472.can-20-3792
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glucose Metabolism Sensitizes Pancreatic Cancer to MEK Inhibition

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is almost universally lethal. A critical unmet need exists to explore essential susceptibilities in PDAC and to identify druggable targets to improve PDAC treatment. KRAS mutations dominate the genetic landscape of PDAC and lead to activation of multiple downstream pathways and cellular processes. Here, we investigated the requirement of these pathways for tumor maintenance using an inducible KrasG12D-driven PDAC mouse model (iKras model), identifying that RAF-MEK-MAPK s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…S2B,C ), indicating that AKT pathway activation is regulated by mTOR pathway as a result of positive feedback rather than by USP21. Moreover, neither forced expression of constitutively activated AKT ( Yan et al 2021 ) nor genetic activation of mTORC1 upstream signaling by Tsc2 depletion was able to drive KRAS* bypass; instead, Tsc2 depletion provoked cell death ( Supplemental Fig. S2D–F ).…”
Section: Resultsmentioning
confidence: 99%
“…S2B,C ), indicating that AKT pathway activation is regulated by mTOR pathway as a result of positive feedback rather than by USP21. Moreover, neither forced expression of constitutively activated AKT ( Yan et al 2021 ) nor genetic activation of mTORC1 upstream signaling by Tsc2 depletion was able to drive KRAS* bypass; instead, Tsc2 depletion provoked cell death ( Supplemental Fig. S2D–F ).…”
Section: Resultsmentioning
confidence: 99%
“…In preclinical studies, 2-DG sensitized cancer cells to multiple types of chemotherapeutic agent [ 41 , 42 , 43 , 44 ], and paclitaxel enhanced the uptake of 2-DG [ 45 ]. 2-DG sensitized pancreatic cancer cells and tumors to inhibition of MEK [ 46 ], the kinase immediately upstream of MAPK3 in the RAS-induced kinase activation cascade. Thus, combining 2-DG with conventional chemotherapies or other agents that induce glycolysis is a reasonable strategy for improving the cancer therapeutics’ efficacies without significantly increasing toxicity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A completed phase I clinical trial evaluated the effect of 2DG alone and in combination with docetaxel on advanced solid tumors ( 87 ). Studies have also shown that low doses of 2-DG inhibition of glucose metabolism combined with a MEK inhibitor induces apoptosis in krasg12d-driven pancreatic ductal adenocarcinoma cells, and experiments also show that this combination treatment inhibited the growth of xenograft pancreatic ductal adenocarcinoma and prolonged total survival ( 103 ).…”
Section: Control Of Cellular Metabolism As a Target For Cancer Therapymentioning
confidence: 99%